Confirmation of a slow symplasmic loading and unloading pathway in barley (Hordeum Vulgare L.) source and sink leaves - Buwa, Lisa Valencia (Rhodes University, Faculty of Science, Botany Department, 2003)
Visualization of the transport pathway in barley (Hordeum vulgare) leaves was carried out using a combination of aniline blue and a symplasmically transported fluorochrome, 5,6 carboxyfluorescein (5,6-CF). When applied to a source leaf, basipetal movement of 5,6-CF was observed after 3 h and the fluorochrome front was observed about 3-4cm away from the point of application. The fluorochrome was taken up into the symplasm of the mesophyll and was loaded into the bundle sheath cells and then subsequently the vascular parenchyma and finally into the sieve tubes. In sink leaves, acropetal movement was observed after 3 h and the fluorochrome had moved approximately 3 cm away from the point of application. Unloading of 5,6-CF occurred from all classes of longitudinal veins. Studies on solute retrieval showed that 5,6 CF-diacetate was transferred to xylem parenchyma where it was metabolized. 5,6-CF was then transferred from the xylem parenchyma to the vascular parenchyma cells, and it would appear that thick-walled sieve tubes were the first to show 5,6-CF labeling. Counterstaining with aniline blue demonstrates the presence of plasmodesmata and this suggests a potential symplasmic pathway from the mesophyll to the sieve tubes. Application of 5,6 CF-diacetate revealed a slow symplasmic pathway, which involved transfer of 5,6-CF, which was effected via plasmodesma.
Keywords: Phloem; Plant translocation; Barley -- Metabolism